The effectiveness of the surgical helmet system in reducing infection and contamination in arthroplasty procedures: An integrative review - Jai Matthews-Cox; Paula Foran (Journal of Perioperative Nursing)
Background: Peri-prosthetic joint infections are a serious complication of primary arthroplasty procedures. While surgical helmet systems are commonly used, limited guidelines exist to support their effectiveness in preventing infection.